Optimalisasi Pencahayaan Alami Melalui Penerapan Void dan Skylight pada Gedung Terpadu UIN Sunan Kalijaga - Nimas Violina; Mohammad Sahid Indraswara; Chely Novia Bramiana (Jurnal Sipil dan Arsitektur, 2025)
Energy consumption in the building sector, especially for lighting systems in tropical climates like Indonesia, is a crucial issue. The Integrated Building of UIN Sunan Kalijaga faces significant challenges regarding visual comfort and energy efficiency due to non-responsive facade design, resulting in low daylight penetration ("room within a room" problem) and potential glare in perimeter areas. This study aims to redesign the building using a passive design approach to improve Daylighting performance to meet SNI 6197:2020 standards. The method used is descriptive quantitative and quasi-experimental with DIALux evo simulation. Redesign strategies focus on passive interventions, including layout shifting, creation of vertical Voids and central Skylights for top-lighting, as well as optimization of Curtain Walls and shading systems. Post-redesign simulation results show that these interventions significantly increase the average Illuminance (E average) to >350 Lux and achieve a more uniform light distribution according to the target. These findings are translated into Technical Design Studies (DED, RKS, and RAB) as a guide for implementing measurable passive architecture solutions.Keywords : Passive Redesign, Daylighting, DIALux evo, SNI 6197:2020, Technical Design Study, Void.